LINGUACULTUROLOGICAL ANALYSIS OF CONCEPT AND CONCEPT OF HAPPINESS - Nizomov Sherbek Zarifjon ogli (Scholars Digest Publishing, 2023)
This article presents a linguaculturological analysis of the concept and perception of happiness. The study aims to explore how the linguistic and cultural factors influence the understanding and expression of happiness across different societies. The research employs a multidisciplinary approach, combining linguistic analysis, cultural studies, and psychological perspectives. The findings contribute to a deeper comprehension of the complexities associated with the concept of happiness, highlighting the diverse cultural nuances and linguistic variations that shape its understanding. The article concludes with implications for fostering well-being and suggests avenues for future research.